Sprint interval training on constant work rate high intensity exercise: time to task failure, biomolecular glycolytic pathway and neuromuscular function adaptations. - Poli, Rodrigo de Araujo Bonetti de [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
The present thesis has been divided into two independent studies. The first study aimed to examine the impact of a 5-week sprint interval training (SIT) on glycolytic response (i.e., glycolytic enzyme content and activity, and glycogen content) and its relationship with time to task failure (TTF) during constant load exercise (CWR) performed above critical intensity. METHODS: In this study, 14 physically active men were randomized into the SIT group (SITG; n=8; 3 times a week, 4-6 efforts of 30-second Wingate) over 5 weeks, and a control group (n=6). Initially, participants underwent: i) an incremental ramp test to measure cardiorespiratory function; ii) CWR cycling at 150% of power output associated with the respiratory compensation point (RCP-PO) with muscle biopsies at rest and immediately after task failure. After 5 weeks, the same assessments were repeated. Glycogen phosphorylase (GPhos), hexokinase (HK), phosphofructokinase (PFK), lactate dehydrogenase (LDH) enzyme content and activities, as well as glycogen content, were analyzed. RESULTS: Content and activity of GPhos, HK, PFK, LDH enzymes, as well as glycogen content, improved post-training only in SITG; however, no difference in glycogen utilization was observed between groups or over time. Additionally, no difference in TTF was observed when CWR was adjusted to post-training physical condition. The second study aimed to investigate whether 5 weeks of SIT could improve neuromuscular function [NMF; maximal voluntary isometric contraction (iMVC) + peripheral nerve stimulation (PNS) with evoked force assessment and electromyography (EMG)] and TTF during CWR performed above critical intensity. METHODS: 21 physically active men participated in the study, randomly allocated to SITG (n=11) and control group (n=10). The experimental design was similar to the first study; however, instead of muscle biopsy, iMVC + PNS + EMG were performed to verify neuromuscular function. RESULTS: SIT did not induce changes in NMF measured by iMVC, as well as in fatigue and EMG signal during CWR. No significant changes in TTF corresponding to the current 150% of RCP-PO were observed. However, SITG showed a significant improvement over time in training outcomes (dynamic neuromuscular function; maximum power and peak power). THESIS CONCLUSION: 5 Weeks of SIT were effective in causing changes in the analyzed glycolytic variables and dynamic neuromuscular function; however, these changes do not seem to underpin the maintenance of exercise tolerance during severe-intensity efforts.

A presente tese foi dividida em dois estudos independentes. O primeiro estudo teve como objetivo examinar o impacto de um treinamento intervalado de sprint (SIT) de 5 semanas na resposta glicolítica (ou seja, conteúdo e atividade enzimática glicolítica e conteúdo de glicogênio) e sua relação com o tempo até a falha na tarefa (TTF) durante o exercício de carga constante (CWR) realizado acima da intensidade crítica. MÉTODOS: Neste estudo, 14 homens fisicamente ativos foram randomizados no grupo SIT (SITG; n=8; 3x semanais de 4-6 esforços de 30-s Wingate) ao longo de 5 semanas, e um grupo de controle (n=6). No início, os participantes foram submetidos a: i) um teste incremental de rampa para medir a função cardiorrespiratória; ii) CWR de ciclismo TTF a 150% da potência associada ao ponto de compensação respiratória (RCP-PO) com biópsias musculares em repouso e imediatamente após a falha na tarefa. Após as 5 semanas, as mesmas avaliações foram repetidas. O conteúdo e as atividades enzimáticas de glicogênio fosforilase (GPhos), hexoquinase (HK), fosfofrutoquinase (PFK) e lactato desidrogenase (LDH), assim como o conteúdo de glicogênio, foram analisados. RESULTADOS: O conteúdo e atividade das enzimas GPhos, HK, PFK, LDH, bem como o conteúdo de glicogênio também melhoraram pós-treinamento apenas no SITG, entretanto, nenhuma diferença foi verificada na utilização de glicogênio foi observada entre os grupos ou ao longo do tempo. Além disso, nenhuma diferença no TFF foi verificada quando o CWR foi realizado ajustado à condição física pós-treinamento. O segundo estudo teve como objetivo investigar se 5 semanas de SIT poderiam melhorar a função neuromuscular [NMF; contração voluntária máxima isométrica (iMVC) + estimulações de nervos periféricos (PNS) com avaliação de força evocada e sinal de eletromiografia (EMG)] e TTF durante o CWR realizado acima da intensidade crítica. MÉTODOS: participaram do estudo 21 homens fisicamente ativos, sendo andomicamente alocados no SITG (n=11) e no grupo de controle (n=10). O desenho experimental foi realizado de forma semelhante ao primeiro estudo; no entanto, em vez de uma biópsia muscular, foi realizado iMVC + PNS + EMG, para verificação da função neuromuscular. RESULTADOS: O SIT não induziu alterações na NMF medida pelo iMVC, assim como na fadigabilidade e no sinal de EMG durante o CWR. Também não foram verificadas alterações significativas no TTF correspondente aos atuais 150% de RCP-PO. Entretanto, o SITG mostrou uma melhoria significativa ao longo do tempo nos resultados dos treinos (função neuromuscular dinâmica; potência máxima e potência pico). CONCLUSÃO DA TESE: 5 semanas de SIT foram eficazes em causar alterações nas variáveis glicolíticas analisadas e na função neuromuscular dinâmica, entretanto essas alterações parecem não fundamentar a manutenção da tolerância ao exercício em esforços de intensidade severa.
Treino intervalado de sprint em exercício de alta intensidade com taxa de trabalho constante: tempo até a falha na tarefa, adaptações na via glicolítica biomolecular e função neuromuscular.
Keywords: High intensity exercise; Exercise tolerance; Glycolytic pathway; Fatiguability